Efficient production of succinic acid from duckweed (Landoltia punctata) hydrolysate by Actinobacillus succinogenes GXAS137. (February 2018) - Shen, Naikun; Zhang, Hongyan; Qin, Yan; Wang, Qingyan; Zhu, Jing; Li, Yi; Jiang, Ming-Guo; Huang, Ribo
Highlights: SHF, SSF and SSSF strategies for SA production from duckweed were evaluated. Multi-enzyme cocktail was optimised to reduce viscosity of duckweed mash. The maximum viscosity reduction of 83.86% was gained. SSSF strategy yielded the highest SA concentration. 75.46 g/L SA was obtained from 180 g/L substrate in a 2 L bioreactor. Abstract: A novel process of enzyme pretreatment and semi-simultaneous saccharification and fermentation (SSSF) was developed in this work to improve succinic acid (SA) productivity from duckweed ( Landoltia punctata ) and achieve low viscosity. Viscosity (83.86%) was reduced by the pretreatment with combined enzymes at 50 °C for 2 h to a greater extent than that by single enzyme (26.19–71.75%). SSSF was an optimal combination with 65.31 g/L of SA content, which was remarkably higher than those obtained through conventional separate hydrolysis and fermentation (62.12 g/L) and simultaneous saccharification and fermentation (52.41 g/L). The combined approach was effective for SA production. Approximately 75.46 g/L of SA content with a yield of 82.87% and a productivity of 1.35 g/L/h was obtained after 56 h in a 2 L bioreactor. Further studies will focus on increasing the working scale of the proposed method.